2014
DOI: 10.1186/1472-6874-14-128
|View full text |Cite
|
Sign up to set email alerts
|

Natural history of ovarian endometrioma in pregnancy

Abstract: BackgroundOvarian endometriomas are classified as benign ovarian lesions. During pregnancy endometriomas may undergo major morphological changes which are referred to as ‘decidualisation’. Decidualised ovarian endometrioma may resemble malignant ovarian tumours on ultrasound examination. The aim was to study variations in the morphology and size of ovarian endometriomas diagnosed on ultrasound during pregnancy.MethodsWe searched our database to identify pregnant women who were diagnosed with ovarian endometrio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
26
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 34 publications
1
26
0
Order By: Relevance
“…Ovarian endometrioma was reported in seven cases, but extrapolation from literature reports suggests that it is likely that these were under-reported (69). Pateman et al (70) reported that the majority of endometriomas were observed to regress during pregnancy when followed up by serial ultrasound and that 12% of cases showed evidence suggestive of decidualization, such as a thick and irregular inner wall, papillary projections, and high vascularity on Doppler examination. These features can pose diagnostic challenges because they may mimic ovarian malignancy.…”
Section: Risk Of Ovarian Endometrioma In Shipmentioning
confidence: 97%
“…Ovarian endometrioma was reported in seven cases, but extrapolation from literature reports suggests that it is likely that these were under-reported (69). Pateman et al (70) reported that the majority of endometriomas were observed to regress during pregnancy when followed up by serial ultrasound and that 12% of cases showed evidence suggestive of decidualization, such as a thick and irregular inner wall, papillary projections, and high vascularity on Doppler examination. These features can pose diagnostic challenges because they may mimic ovarian malignancy.…”
Section: Risk Of Ovarian Endometrioma In Shipmentioning
confidence: 97%
“…The results of these reports are confusing with 15% to 50% of endometriotic lesions disappearing, 34% to 65% regressing and the remaining lesions either increasing (9% to 39%) or remaining unchaned (25%) during pregnancy. Anecdotal reports also describe reduction of non-ovarian lesions or regression of endometriotic lesions during the early puerperium period, however, the majority of lesions seem not to regress (3).…”
mentioning
confidence: 99%
“…The few available studies support regression more often in the second or third than in the trimester or the lactation period. Imaging and histopathology studies of endometriotic lesions during pregnancy show that they may grow rapidly during pregnancy, making differentiation from malignant tumours challenging (3). The enlargement of endometriotic lesions and suspicious sono-morphological appearance is the most frequent reason for surgical interventions during pregnancy.…”
mentioning
confidence: 99%
See 2 more Smart Citations